False self‐employment: the case of Ukrainian migrants in London's construction sector. Issue 1 (27th February 2018) - Vershinina, Natalia A.; Rodgers, Peter; Ram, Monder; Theodorakopoulos, Nick; Rodionova, Yulia
Abstract: This article, presenting qualitative accounts of Ukrainian business owners, highlights how migrants engage in false self‐employment in the UK. Their experiences problematise notions of legality and binary depictions of migrant workers as 'victims or villains', demonstrating that migrants see their illegal status as a transient stage before gaining legal status.